A Descriptive Correlational Survey to Assess the Knowledge Related to Prevention of Nosocomial Infections and Selected Practices among Staff Nurses in a Selected Hospital of New Delhi (Medico Legal Update, 2020)
A Descriptive Correlational Survey to assess the knowledge related to prevention of Nosocomial Infectionsand selected practices among staff nurses in selected nursing care units of a selected Hospital of NewDelhi. The objectives of the study were to assess knowledge and selected practices of staff nurses regardingprevention of nosocomial infections, to seek relationship between knowledge and hand washing practice, toseek relationship between knowledge and IV injection practice and to seek association between knowledge,hand washing practice and IV injection practice with their demographic variables. 60 staff nurses wereselected by using convenient sampling. A knowledge questionnaire and two observational checklists weredeveloped to determine the knowledge and selected practices related to hand washing and IV injectionprocedure. Knowledge questionnaire consisted of 30 items and two observational checklists for handwashing procedure consisted of 12 items and IV injection procedure consisted of 21 items. After obtainingpermission from Administrative and Ethical committee, the data collection was done in the month of Dec.-Jan. The findings of the study revealed that mean percentage of knowledge seen (62.73%), mean percentageof hand washing practice seen (61.42%) and mean percentage of IV injection practice seen (53.19%). KarlPearson correlation was used to check the relationship between knowledge and selected practices showedthere was no significance between knowledge and practice scores. Statistical significance were only foundbetween knowledge scores with variable like no. of times attended in service education but there was nosignificance found with other variables. Also, there was statistical significance found between hand washingpractice and IV injection practice with variable like current area of posting but there was no associationfound with other variables. Based on the findings, recommendations proposed for future research.